Realization of a Single-Phase Multilevel Inverter for Grid-Connected Photovoltaic System - Nouaiti, A.; Mesbahi, A.; Saad, A.; Khafallah, M.; Reddak, M. (Engineering, Technology & Applied Science Research, 2018)
This paper introduces the implementation of a single-phase multilevel inverter for a grid-connected photovoltaic system. The considered topology contains a full bridge converter tied to an auxiliary circuit made of two power switches. A proportional integral (PI) current controller is established with this inverter to inject a sinusoidal current into the grid with a power factor near to unity. The studied system is tested on Matlab/Simulink and verified by experiment through a test bench comprising of a fabricated prototype and a DSP TMS320F28379D. The obtained results prove the efficiency of the inverter to maintain a direct power flow from DC sources, such as solar panels, to the grid by respecting some normalized criteria for this operation.